STRATEGI MENDONGENG UNTUK MENINGKATKAN KEMAMPUAN VERBAL SISWA DI TK DARUL MUHSININ - Sarilah, Sarilah; Sulastri, Ni Made; Iman, Nurul; Herlina, Herlina (Fakultas Ilmu Pendidikan dan Psikologi, 2024)
The level of education in Indonesia is still dominated by low-educated people. There are various factors that cause children in Indonesia not to have a good education, namely the low quality of physical facilities. Learning in kindergarten can be developed using various methods, one of which is the storytelling method. Fairy tales are simple stories that don't really happen. Fairy tales function to convey morals (educate) and also entertain. Storytelling activities will be able to increase children's growth and development and develop various kinds of children's creativity, one of the creativity that can be developed is verbal creativity. Verbal creativity is the ability to form new ideas or thoughts, and combine these ideas into something new based on existing information or elements. So it is felt necessary to carry out storytelling activities to improve children's verbal abilities. The method used in current service activities is in the form of direct practice in the form of storytelling activities using various media such as picture books, hand puppets, the use of vocal techniques and can also bring in storytellers or fairy tale experts, so that the storytelling activities are more interesting. The result of this storytelling activity is that there is an increase in children's verbal abilities after and during the storytelling activity, and for schools it can be an innovation in the learning process.